Les choix monétaires européens 1950-1980 - Abraham, J.-P.; Lemineur-Toumson, C. (Études internationales, 1981)
This article focuses on three key dates in analyzing the monetary policy options arrived at by the States of Europe over the course of the last thirty years. By the creation of the European Payments Union in 1958, the European States made a regionalist policy option by establishing the intra-European convertibility of their currencies while maintaining exchange restrictions with respect to the dollar zone. In 1958 on the other hand resumption of general convertibility of currencies demonstrated the "global-linkage" policy option of the decision-makers of the period by removing any specifically European substance from the European monetary agreement. From this perspective, the decision of December 1978 to institute a monetary System would clearly appear to be by far the most important initiative taken in some time to reestablish a framework for European monetary cooperation. With regard to international monetary relations, eight countries have therefore, within three decades, chosen two regionalist policy options and one global-linkage policy option. The purpose of this study is to identify the circumstances, reasons and impact of the policy options that have successively been implemented.